Functional heterogeneity in a plant–frugivore assemblage enhances seed dispersal resilience to habitat loss - García, Daniel (2013)
The ability of ecosystems to maintain their functions after disturbance (ecological resilience) depends on heterogeneity in the functional capabilities among species within assemblages. Functional heterogeneity may affect resilience by determining multiplicity between species in the provision of functions (redundancy) and complementarity between species in their ability to respond to disturbances (response diversity), but also by promoting the maintenance of biological information that enables ecosystems to reorganize themselves (ecological memory). Here, we assess the role of the components of the functional heterogeneity of a plant–frugivore assemblage on the resilience of seed dispersal to habitat loss. For three years, we quantified the distributions of fruits, frugivorous thrushes (Turdus spp.) and dispersed seeds, as well as frugivore diet and movement, along a gradient of forest cover in N Spain. The abundances and the spatial distributions of fruits and birds varied between years. The different thrushes showed similar diets but differed in spatial behavior and response to habitat loss, suggesting the occurrence of both functional redundancy and response diversity. Forest cover and fruit availability affected the spatial distribution of the whole frugivore assemblage. Fruit tracking was stronger in years when fruits were scarcer but more widespread across the whole fragmented landscape, entailing larger proportions of seeds dispersed to areas of low forest cover and open microhabitats. Rather than depending on redundancy and/or response diversity, seed dispersal resilience mostly emerged from the ecological memory conferred by the inter-annual variability in fruit production and the ability of thrushes to track fruit resources across the fragmented landscape. Ecological memory also derived from the interaction of plants and frugivores as source organisms (trees in undisturbed forest), mobile links (birds able to disperse seeds into the disturbed habitat), and biological legacies (remnant trees and small forest patches offering scattered fruit resources across the landscape).